Clinical Pharmacology of Hormonal Emergency Contraceptive Pills - Matyanga, Celia M. J.; Dzingirai, Blessing (International Journal of Reproductive Medicine, 2018)
Emergency contraceptives play a major role in preventing unwanted pregnancy. The use of emergency contraceptives is characterized by myths and lack of knowledge by both health professionals and users. The main objective of this paper is to summarize the clinical pharmacology of hormonal methods of emergency contraception. A literature review was done to describe in detail the mechanism of action, efficacy, pharmacokinetics, safety profile, and drug interactions of hormonal emergency contraceptive pills. This information is useful to healthcare professionals and users to fully understand how hormonal emergency contraceptive methods work.